DETERMINAN PENGANGGURAN ANTAR KABUPATEN/KOTA DI JAWA BARAT - Kharisma, Bayu; Wardhana, Adhitya; Lathifah, Syafira Nur (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.04.TAHUN.2021DO - 10.24843/EEB.2021.v10.i04.p06, 2021)
This study aims to analyze the determinant of unemployment between districts / cities in West Java during the period 2011-2017. The research method used is data panel regression through fixed effect model. The results showed that the mean of year schooling and economic output were negative, while poverty and population had a positive relationship to unemployment. Aspects of education have an influence in lowering unemployment. Therefore, the need to increase the mandatory nine-year study target as an effort to improve the quality of human resources, especially for regions that have not reached the target. Furthermore, the policy of accelerating the economy by increasing its economic output and maintaining the population level in order to strike a balance in employment and unemployment so as not to continue to increase.